IDENTIFIKASI KANDUNGAN FORMALIN PADA KUE YANG BEREDAR DI PASAR TRADISIONAL PERUMNAS KLENDER JAKARTA TIMUR - Tria Prayoga; Pricillya Maria Loimalitna; Ivan Santoso; Asfiati Asysyifaa (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
Based on BPOM, in Indonesia there are around 20 million cases of food poisoning per year. Palembang's BPOM agency also found market snacks, kue apem cakes and a number of other foods to contain formalin. BTP (Food Additives) which are often used in food processing are preservatives such as formalin. Formalin is used because it can extend the shelf life of the food. This study aims to test the alleged presence of formaldehyde in samples of wet cakes circulating in Klender Market, East Jakarta. The method used in this study is the identification of formalin compounds by qualitative chemical analysis using Schiff's reagent. In this study, it was found that samples of apem cakes, cucur cakes and putu ayu cakes from the Perumnas Klender Traditional Market, East Jakarta, did not contain formalin compounds.